A review on cutting fluids used in machining processes. (18th March 2021) - Singh, Jasjeevan; Gill, Simranpreet Singh; Dogra, Manu; Singh, Rupinder
Abstract: Cutting fluids provide cooling at the cutting tool and on the surface of work piece, lubricate the tool-workpiece interface and evacuate chips from the cutting zone in the machining processes. The primary reason for using cutting fluid is to reduce the temperature at cutting zone and friction wear either through cooling or lubrication. To maximize the efficiency of cutting fluids in machining processes the knowledge of machining conditions and cutting fluid types are critically important. However, misemploy of the cutting fluid and non efficient method of disposal can raise health issues and environmental impact. In this paper, an attempt has been made to provide overview of cutting fluids type, cooling techniques and main alternatives as dry machining, cryogenic cooling, minimum quantity lubrication and hybrid cooling minimizing use of cutting fluids. The inclusion of solid lubricants, nano fluids in lubrication/cooling techniques results in increase in the productivity of the process due to reduction in friction and heat at the cutting zone. The cutting parameters and type of tools utilized by various researchers have been summed up and introduced in this paper to provide useful information to various researcher works.